Effect of simulated warming on the functional traits of Leymus chinensis plant in Songnen grassland. Issue 6 (8th November 2019) - Guo, Rui; Zhou, Ji; Zhong, Xiuli; Gu, Fengxue; Liu, Qi; Li, Haoru
Abstract: Leymus chinensis grassland in Northeast China provides a natural laboratory for the investigation of climate change. The response of L. chinensis to experimental warming can provide insight into its regeneration behaviour and the likely composition of future communities under warmer climate. We used MSR-2420 infrared radiators to elevate temperature and examined soil organic carbon and nitrogen and soil total phosphorus and determined the growth and physiology of L. chinensis in response to manipulations of ambient condition and warming. Results showed that compared with the control, L. chinensis subjected to warming treatment showed increased soil organic carbon and soil total nitrogen, but no significant difference was observed in soil total phosphorus. Climate warming increased shoot biomass, ecosystem respiration, and ecosystem water-use efficiency and reduced net ecosystem CO2 exchange and evapotranspiration. This result implies that warming could rapidly alter carbon fluxes. The effect of warming treatment significantly increased the contents of glucose and fructose and significantly inhibited sucrose synthesis. However, the TCA cycle was enhanced when citric and malic acid contents further accumulated. The results implied that L. chinensis probably enhanced its warming adaption mechanism mainly through increasing glycolysis consumption when it was exposed to elevated temperature. These results provide an understanding of the fundamental evidence explaining the primary metabolism of L. chinensis in response to warming and suggest the future impact of the terrestrial carbon-cycle feedback on global climate change. Abstract : Understanding how grasses are affected by a long-term increase in temperature is crucial to understanding the future impact of global climate change. Measurements of soil properties, ecosystem gas exchange and physiological characteristics were made in Leymus chinensis grassland under elevated temperatures. The result showed that warming increased the soil organic carbon, soil total nitrogen, shoot biomass, ecosystem respiration and ecosystem water-use efficiency, but reduced net ecosystem CO2 exchange and evapotranspiration. This result implies that warming could rapidly alter carbon fluxes, and L. chinensis probably enhanced its warming adaptation mechanism mainly through increasing glycolysis consumption.